Using of phosphatized dolomite for treatment of real mine water from metal ions. (February 2016) - Ivanets, A.I.; Kitikova, N.V.; Shashkova, I.L.; Oleksiienko, O.V.; Levchuk, I.; Sillanpää, M.
Abstract: The aim of this paper was to study the sorption properties of Ca–Mg phosphate sorbents using real mine water, containing bi- and trivalent metal ions such as Al 3+, Cr 3+, Ni 2+, Mn 2+, Co 2+, Pb 2+, Cu 2+, Cd 2+, Zn 2+ and Fe 3+ . The sorbents utilized in this work were prepared from dolomite and represent a mixture of Ca 2+ and Mg 2+ hydrogen phosphates (PD-1) and tertiary phosphates of Ca 2+ and Mg 2+ (PD-2). The synthesized sorbents were characterized by X-Ray diffraction, Fourier transforms infrared spectroscopy, differential-thermal analysis, thermogravimetric analysis, and low temperature adsorption-desorption of nitrogen methods. Sorption experiments were conducted in batch mode. Removal efficiency dependencies on sorbent dose, nature of the metal ion, contact time and temperature were established. For both tested materials the highest level of mine water purification was achieved at the sorbent dose of 25 g L −1, leading to the elimination of all metal ions except Mn 2+ when PD-2 was used and Cd 2+ and Co 2+ in the case of PD-1. The sorption kinetics of PD-1 and PD-2 were evaluated with a pseudo-second order kinetic model. It was observed that raising the temperature from 15 to 40 °C leads to increased removal efficiency for all studied metal ions. The results of this study indicate that the prepared sorbents are highly effective for the treatment of multi-component mine water.